2005
DOI: 10.1021/ja052876h
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Resolutions of Azomethine Imines via Copper-Catalyzed [3 + 2] Cycloadditions

Abstract: An effective method has been developed for the kinetic resolution of racemic azomethine imines via [3 + 2] cycloadditions with alkynes catalyzed by a chiral copper complex. Efficient kinetic resolution is observed for a variety of N1 and C5 substituents on the dipole, thereby furnishing a wide array of useful enantioenriched azomethine imines, which can readily be transformed into monocyclic and bicyclic pyrazolidinones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(62 citation statements)
references
References 8 publications
(7 reference statements)
2
59
0
1
Order By: Relevance
“…In an extension of this method, it has been shown that the same catalyst system is also effective in the kinetic resolution of racemic azomethine imines rac-65 (Scheme 17) [86]. As a result, a wide variety of enantioenriched 1,3-dipoles 65 could be isolated.…”
Section: Enantioselective [3+2] Cycloadditionsmentioning
confidence: 99%
“…In an extension of this method, it has been shown that the same catalyst system is also effective in the kinetic resolution of racemic azomethine imines rac-65 (Scheme 17) [86]. As a result, a wide variety of enantioenriched 1,3-dipoles 65 could be isolated.…”
Section: Enantioselective [3+2] Cycloadditionsmentioning
confidence: 99%
“…This copper(I)-catalyzed asymmetric cycloaddition was employed in the kinetic resolution of racemic azomethine imine 175 by using phenyl-substituted phosphaferrocene oxazoline L 17 as the ligand, leading to chiral azomethine imine 176 (Scheme 31). [62] By altering the catalyst to copper bis(trimethylsilyl)amide (CuHMDS) and (S)-DIP-BINAP L 10 , Kobayashi and co-workers reported another example for the copper-catalyzed 1,3-dipolar cycloaddition, affording 5,7-disubstituted pyrazolo-A C H T U N G T R E N N U N G [1,2-a]pyrazolones 162 exclusively. In this transformation, the regioselectivity was reversed compared with the results reported by Fu and co-workers.…”
Section: A C H T U N G T R E N N U N G [3+2] Cyclization Of N-imide Ymentioning
confidence: 99%
“…(34)), thereby furnishing enantioenriched azomethine imines that can be transformed into a variety of pyrazolidinones (Eq. (35) and (36)) [76]. Phosphaferrocene-oxazoline 75 provided the highest selectivity factors among an array of chiral ligands that were examined.…”
Section: Copper-catalyzed Cycloadditionsmentioning
confidence: 99%